The Important of Language Learning in the Curriculum of 2013 - Mawaddah Warahmah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Curriculum 2013 which has been set in this year continues to be an interesting discussion in various forums . Variety grown in the public discourse related to the curriculum in 2013 is very rampant, of course based on their perspective . Many perceptions that need to be appreciated as part of the maturation process of the curriculum that is being compiled and correlate with learning a new language provides a means of communicating with people from another culture and exploring one’s own personal world. Languages are inseparably linked to the social and cultural contexts in which they are used. Languages and cultures play a key role in developing our personal, group, national, and human identities. Every language has its own ways of expressing meanings; each has intrinsic value and special significance for its users.